(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
The primary and secondary education is fully missing the teaching of the legal knowledge subjects belonging to basic literacy. Due to the lack of this, the functioning of the state-organization and the self-government, the basic human and civil rights and responsibilities are not understandable. The teacher students who begin their higher education studies – and often get through it –do not understand the basic social operations and concepts (the structure and operation of the parliament, government, self-governments, Constitutional Court, court, prosecution etc.; orientation in public administration etc.). The educated teacher is the member of the child protection warning system because of his/her job. In this context he/she is encumbered by hailing obligations based on many legislations. They cannot meet their obligation without knowing the basic family and child protection laws. This omission entails responsibility for the labor and criminal law. We can hear about this kind of occasions and omissions from the previous and current news on daily basis. The presentation presents the neccesity of the legal subjects in the basic pedagogical training.